Pengaruh Penghindaran Pajak Jangka Panjang terhadap Nilai Perusahaan dengan Kepemilikan Saham Institusional sebagai Variabel Pemoderasi - Tama, I Gede Riko; Setiawan, Putu Ery; Jati, I Ketut (E-Jurnal Akuntansi; Vol 23 No 2 (2018)DO - 10.24843/EJA.2018.v23.i02.p05, 2018)
This study aims to analyze the effects of long-term tax avoidance on corporate value and to analyze institutional share ownership can moderate the effect of long-term tax avoidance on firm value. The method of determining the sample using purposive sampling is the sampling based on subjective considerations of the researcher, where there are conditions that must be met by the sample. Data collection is done through the collection of data contained in the annual financial statements related to this research. The analysis technique used is Moderated Regression Analysis (MRA). Based on the analysis result, it is concluded that long-term tax avoidance has a negative and nonsignificant effect on corporate value and institutional share ownership is not able to moderate the effect of long-term tax avoidance on the value of companies in manufacturing companies listed on the BEI period 2006-2016.